Psychosocial Intervention untuk Meningkatkan Kualitas Hidup Caregiver dalam Merawat Pasien Kanker - Astika Irmawaty Sigalingging; Elly Nurachmah; Agung Waluyo (FORIKES, 2024)
The burden of caregivers of cancer patients affects their quality of life, thus affecting their attitudes and actions in providing care to cancer patients. Appropriate interventions are needed to maintain quality of life and support caregivers in providing care to cancer patients. This study aimed to determine the effectiveness of psychosocial intervention on the quality of life of caregivers in caring for patients with cancer. This study was conducted based on PRISMA and identifying the effectiveness of psychosocial intervention for caregivers. Article searches used 5 electronic databases, namely PubMed, Sage, Scopus, ScienceDirect, and Cochrane Library by considering the inclusion criteria. Ten articles obtained were assessed using the JBI Critical Appraisal Tools. Based on the review results of 10 selected articles, it was found that psychosocial intervention is effective in improving the quality of life of caregivers of patients with cancer. The average intervention was carried out 4-5 meetings with a duration of 60-90 minutes. Interpersonal counseling strategies were considered more effective in implementing psychosocial intervention. The use of telephone and videophone technology is an effective tool to facilitate the implementation of interventions. Furthermore, it was concluded that psychosocial intervention is effective in improving the quality of life of caregivers.Keywords: cancer; caregiver; quality of life; psychosocial intervention ABSTRAK Beban caregiver pasien kanker memengaruhi kualitas hidup mereka sehingga berdampak terhadap sikap dan tindakan mereka dalam pemberian asuhan kepada pasien kanker. Intervensi yang tepat diperlukan untuk menjaga kualitas hidup serta mendukung caregiver dalam memberikan perawatan pada pasien kanker. Studi ini bertujuan untuk mengetahui efektivitas psychosocial intervention terhadap kualitas hidup caregiver dalam merawat pasien dengan kanker. Studi ini dilakukan dengan berpedoman pada PRISMA dan mengidentifikasi efektifitas psychosocial intervention bagi caregiver. Pencarian artikel menggunakan 5 database elektronik yaitu PubMed, Sage, Scopus, ScienceDirect, dan Cochrane Library dengan mempertimbangkan kriteria inklusi. Sepuluh artikel yang diperoleh dinilai dengan JBI Critical Appraisal Tools. Berdasarkan hasil review dari 10 artikel terpilih, didapatkan hasil bahwa psychosocial intervention efektif untuk meningkatkan kualitas hidup caregiver pasien dengan kanker. Rerata intervensi dilakukan 4-5 pertemuan dengan durasi 60-90 menit. Strategi konseling interpersonal dinilai lebih efektif dalam penerapan psychosocial intervention. Penggunaan teknologi telepon dan videophone menjadi alat yang efektif memudahkan penerapan intervensi. Selanjutnya disimpulkan bahwa psychosocial intervention efektif untuk meningkatkan kualitas hidup caregiver.Kata kunci: kanker; caregiver; kualitas hidup; psychosocial intervention